Novel histone modifications in microglia derived from a mouse model of chronic pain. Issue 9 (5th February 2022) - Zhang, Ping; Guergues, Jennifer; Alleyne, Amy R.; Cirino, Thomas J.; Nadeau, Owen; Figueroa, Ariana M.; Stacy, Heather M.; Suzuki, Takayoshi; McLaughlin, Jay P.; Stevens, Stanley M.; Liu, Bin
Abstract: As the resident immune cells in the central nervous system, microglia play an important role in the maintenance of its homeostasis. Dysregulation of microglia has been associated with the development and maintenance of chronic pain. However, the relevant molecular pathways remain poorly defined. In this study, we used a mass spectrometry‐based proteomic approach to screen potential changes of histone protein modifications in microglia isolated from the brain of control and cisplatin‐induced neuropathic pain adult C57BL/6J male mice. We identified several novel microglial histone modifications associated with pain, including statistically significantly decreased histone H3.1 lysine 27 mono‐methylation (H3.1K27me1, 54.8% of control) and H3 lysine 56 tri‐methylation (7.5% of control), as well as a trend suggesting increased H3 tyrosine 41 nitration. We further investigated the functional role of H3.1K27me1 and found that treatment of cultured microglial cells for 4 consecutive days with 1–10 μM of NCDM‐64, a potent and selective inhibitor of lysine demethylase 7A, an enzyme responsible for the demethylation of H3K27me1, dose‐dependently elevated its levels with a greater than a two‐fold increase observed at 10 μM compared to vehicle‐treated control cells. Moreover, pretreatment of mice with NCDM‐64 (10 or 25 mg/kg/day, i.p.) prior to cisplatin treatment prevented the development of neuropathic pain in mice. The identification of specific chromatin marks in microglia associated with chronic pain may yield critical insight into the contribution of microglia to the development and maintenance of pain, and opens new avenues for the development of novel nonopioid therapeutics for the effective management of chronic pain.